(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes harmful chemical substances commonly encountered in industrial areas and their effects on human health, with particular emphasis on dental enamel. The anatomical and physiological structure of dental enamel is described, and its sensitivity to chemical agents is substantiated based on scientific sources. Data are presented on how substances released into the atmosphere from industrial enterprises—such as fluoride compounds, acids, heavy metals, sulfate and nitrate oxides—can lead to enamel demineralization, pigmentation, and structural damage. In addition, recommendations for preventive measures aimed at reducing dental problems among populations living in industrial zones are provided.